Academic freedom, university autonomy and admission policy in the Jordanian public universities - Al-Zyoud, Mohammad Sayel Nasr-allah (2001)
This study examines the extent of academic freedom for academics and students, university autonomy and equality of admission in the Jordanian public universities. It examines academic freedom in terms of freedom to express views and ideas, freedom to select course content, freedom to select research subjects, freedom to participate in social and political activities, freedom to participate in decision making and freedom to be promoted from one academic rank to another. Also, it considers university autonomy in terms of admission of students, appointment of academics, establishing new programmes of study and research, administration of students' affairs and university autonomy from the pressure of society. Finally, it examines the admission policy in terms of the equality of the admission criteria; these are the Tawjihi scores and the quota components.